The Improvement of Learning Competency of Skills Lab of Electrocardiography through Academic Motivation and Self-Directed Learning Readiness among Medical Student - Sotya Satmaka Adira; Ratna Kusumawati; Eti Poncorini (Nexus Pendidikan Kedokteran dan Kesehatan, 2017)
Introduction: Academic motivation is the key to generate students readiness to study by their own will, as it calls Self Directed Learning Readiness (SDLR). SDLR can increase students learning input, especially in this case which is the learning process of Skills Lab of Electrocardiography, which has complex learning subject and high number of failed student. This research purpose is to find the correlation of academic motivation with self directed learning readiness. Methods: This research was a cross-sectional observational analytic. Research location was in Faculty of Medicine of Sebelas Maret University. The subjects were medical students of Sebelas Maret University class of 2012, 2013, and 2014 generation. The subjects selected by using proportional stratified random sampling method. Academic motivation was measured by Motivated Strategies for Learning Questionnaire (MSLQ) . SDLR was measured by questionnaire of Self Directed Learning Readiness for Nurse Education (SDLR-NE). The statistical analysis of obtained research data was Pearson Correlation Test. Results: Normality test showed that data of academic motivation and self directed learning readiness was normally distributed. Pearson correlation test result was 0.551 with p = 0.000 Conclusions: This research has showed the correlation between academic motivation and SDLR. Higher of academic motivation value then the SDLR in learning process of Skills Lab of Elctrocardiography value will also be higher. Keywords: Motivation, Academic Motivation, Self Directed Learning Readiness